2015
DOI: 10.1021/acs.inorgchem.5b01434
|View full text |Cite
|
Sign up to set email alerts
|

Mercury- and Cadmium-Assisted [2 + 2] Cyclodimerization of tert-Butylselenium Diimide

Abstract: The complexes [MCl2{N,N'-(t)BuNSe(μ-N(t)Bu)2SeN(t)Bu}] [M = Cd (1), Hg (2)] were obtained in high yields by the reaction of tert-butylselenium diimide Se(IV)(N(t)Bu)2 with CdCl2 or HgCl2 in tetrahydrofuran. Recrystallization of 1 and 2 from acetonitrile (MeCN) afforded yellow crystals of 1·MeCN and 2·MeCN, respectively. Isomorphic 1·MeCN and 2·MeCN contain an unprecedented dimeric selenium diimide ligand, which is N,N'-chelated to the metal through exocyclic imido groups. In addition to the complexes 1 and 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
(44 reference statements)
1
3
0
Order By: Relevance
“…The calculated dimerization energy for the [2 + 2] cycloaddition of two E(NR)2 (E = Se, Te; R = t Bu, SiMe3) molecules is strongly exothermic for tellurium(IV) diimides, but approximately thermoneutral for selenium(IV) diimides, consistent with the experimental observations [75,76]. However, the dimerization of selenium(IV) diimides is promoted by group 12 metal dihalides MCl2 (M = Cd, Hg) to give N,N'-chelated complexes of t BuNSe(µ-N t Bu)2SeN t Bu [77], which are structurally analogous to the HgCl2 complex of the tellurium(IV) diimide dimer t BuNTe(µ-N t Bu)2TeN t Bu [78].…”
Section: Synthesis Structures and Applications In Organic Synthesissupporting
confidence: 83%
“…The calculated dimerization energy for the [2 + 2] cycloaddition of two E(NR)2 (E = Se, Te; R = t Bu, SiMe3) molecules is strongly exothermic for tellurium(IV) diimides, but approximately thermoneutral for selenium(IV) diimides, consistent with the experimental observations [75,76]. However, the dimerization of selenium(IV) diimides is promoted by group 12 metal dihalides MCl2 (M = Cd, Hg) to give N,N'-chelated complexes of t BuNSe(µ-N t Bu)2SeN t Bu [77], which are structurally analogous to the HgCl2 complex of the tellurium(IV) diimide dimer t BuNTe(µ-N t Bu)2TeN t Bu [78].…”
Section: Synthesis Structures and Applications In Organic Synthesissupporting
confidence: 83%
“…43 While the [2 + 2] cyclodimerisation has been deduced to be slightly endergonic in solution, a combination of experimental and computational studies have demonstrated that the cyclodimerisation of the tert-butyl derivative t BuN=Se=N t Bu is facilitated by group 12 metal dihalides MCl2 (M = Cd, Hg). 44 The cyclic, dimeric ligand in the MCl2 complexes formed in this way is structurally analogous to the known structure of the corresponding tellurium(IV) imide, t BuNTe(μ-N t Bu)TeN t Bu, which is dimeric in the solid state, as the free ligand. 45 t BuNSe(μ-N t Bu)SeN t Bu once formed is kinetically inert in solution, as can be deduced from the reaction energetics shown in Fig.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 77%
“…The methods used in the calculation of the organometallic compounds with mercury in the literature have been chosen [19] [20] [21]. It is especially known, M06 is one of the best functional for the study of organometallic and inorganomatellic thermochemistry and noncovalent interactions.…”
Section: Methodsmentioning
confidence: 99%